Hubungan Tingkat Pendidikan Terhadap Kepercayaan Diri Perawat Dalam Melakukan CPR di IGD RSD X - Muthmainnah, Muthmainnah; Maulani, Firman (Journal of Nursing Invention, 2023)
Background: Cardiac arrest is a condition that can result in a person's death. Death from cardiac arrest is the largest contributor to sudden death in the world. 17.9 million people died from cardiovascular disease in 2019, representing 32% of all global deaths. Of these deaths, 85% were caused by heart attacks and strokes (World Health Association (WHO), 2021). In the United States, the incidence of In Hospital Cardiac Arrest (IHCA) is estimated to be around 200 thousand people each year and those who can be saved are only less than 20%. Objective: The purpose of this study was to determine the relationship between education level and nurses' confidence in performing CPR in the emergency room. Method: This study is a cross-sectional correlative research approach. The sampling technique uses a saturated sampling technique with the number of respondents as many as 32 people. Research instruments in the form of questionnaires and statistical tests using spearman rank. Results: The statistical results of the spearman rating test showed that education (p = 0.046) so it can be concluded that there is a relationship between the level of education and the confidence of nurses who give CPR in the emergency room. Conclusion: The result of the strength of the relationship is strong where the higher the level of education and the higher the confidence of the nurse giving CPR.